Eficiência do tratamento das sementes na redução das "falhas" em plantio de algodão mocó - Ponte, J.J. da. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
In this paper the author studied the behavior of the "moco" cotton seeds, Gossypium hirsutum Marie-Galante Hutch., in the dissemination of the fungus Colletotrichum gossypii South., in the State of Ceara, Brazil. The results analyzed statistically showed the following conclusions: The "moco" cotton seeds have, at the present time, considerable influence in the dissemination of the fungus. This fact has contributed to a frequent incidence of the "damping-off" in the new cotton crop. The treatment of the seeds by concentrated sulphuric acid has an efficient control of the "damping-off", caused by Colletotrichum gossypii South. The location of the fungus within the seed has very seldom contributed to its dissemination. A treatment by physical means is not necessary because of this fact.